Efeitos da contaminação fecal sobre a dinâmica e a estrutura da alça microbiana em areias de praias do litoral norte do estado de São Paulo - Pereira, Cristina Rocha [UNESP] (2014)
The increasing development of tourism in coastal regions can generate various impacts to the environment, which only recently has been devoted sufficient attention. Organic pollution may affect microbial communities with consequences spread through the entire pelagic food webs and affecting biogeochemical cycles. There are few studies about microbial ecology in beach sands in Brazil. The aim of this study was to compare the microbial dynamics in sands of two beaches with distinct degrees of sewage input, to infer possible effects of sewage pollution and physical and chemical factors over microbial loop. Beach sand samples were collected during 24 hours in the summer and winter from Domingas Dias and Itaguá beaches, Ubatuba city, São Paulo State. The samples were analysed for heterotrophic bacteria, cyanobacteria, heterotrophic and autotrophic nanoflagellates, and heterotrophic and autotrophic microplankton interactions and densities, Enterococcus sp. and Escherichia coli densities, organic matter quantity, granulometry and temperature. Differences were seen between the densities of the microorganisms from the beaches of Domingas Dias and Itaguá. Changes in the fluctuations of the microorganisms of the microbial loop showed that the structure and dynamics may suffer resulting changes of several factors, alone or together as the discharges of organic wastewater, the amount of organic matter and temperature values of the sediment. The microbial loop is shown to have an important role in the transfer of matter and energy to higher levels of the food chain, especially in oligotrophic periods of the year, occurring seasonal alternations of food depending on the activities of predators and trophic status of environmental pollution